SystemC Methodologies and Applications - Müller, Wolfgang; Rosenstiel, Wolfgang; Ruf, Jürgen (Springer US, 2003)
SystemC has received a wide acceptance by users and tool vendors as the next generation system description language in order to deal with higher levels of abstraction for complex SoC designs. SystemC Methodologies and Applications gives a comprehensive survey on the state of the art of SystemC in industry and research. Organised into 11 self-contained chapters, selected SystemC experts present their approaches in the domains of -modelling, -analysis, -synthesis. Their contributions range from mixed signal and discrete system to embedded software. The chapters give a broad overview of recent advances in SystemC methodologies and applications and are mainly based on presentations given at the European SystemC User Group meetings